Analisis Pembiayaan Kesehatan Program Kesehatan Ibu dan Anak (KIA) Berdasarkan Standar Pelayanan Minimal (SPM) di Kabupaten Nunukan - Mustaqim Hariyadi; Julita Hendrartini; M.Arief Budiarto (Center for Health Policy and Management, 2015)
Background: The role of regional government in decentralization period is very important to the health sector particularly in financing. This is because health is one of the sectors that was decentralized. Minimum service standard is the obligatory responsibility for the region that is the right of every citizen at a minimum level, and one of many basic services is Maternal and Child Health programs. Objectives: To asses the financing sufficiency for Maternal and Child Health Programs based on Minimum Service Standard cost calculation and the effectivity of financing for Maternal and Child Health programs to achieve program’s objectives and goals. Methods: This research is a descriptive study conducted in Nunukan in 2013 with quantitative data. Sufficiency analysis is done by calculating the cost of Maternal and Child Health program to the result of cost calculation based on Minimum Service Standard. Performance effectivity of the Maternal and Child Health Programs was analyzed by the achievement of Minimum Service Standard according to the national indicator target and Maternal Mortality and Infant Mortality to the target of RPJMN of 2010-2014. Results: The cost of Maternal and Child Health program that was available was Rp. 2.530.038.761, and the calculation result of the cost based on Minimum Service Standard at Rp. 3.707.719.364, thus there was fund deficit about Rp 1.177.680.603. The percentage of MCH programs financing by the central government was still hight that was about 75%. There are financing MCH programs for direct activities amounted to 74%, and indirect activities amounted to 26%. The financing performance of MCH program was not effective yet to achieve the target of national Minimum Service Standard indicator and maternal mortality was still high at 173 per 100.000 life birts and infant mortality at 14 per 1000 live births. Conclusion: The financing of MCH programs was not sufficient to perform activities in MCH programs, as there was fund deficit about Rp 1.177.680.603. There was high financing dependency to the central government at 75% because of the low regional government commitment to financing priority programs such as MCH programs.